CMV-Specific Cell-Mediated Immunity Predicts a High Level of CMV Replication After Prophylaxis Withdrawal in Lung Transplant Recipients. (27th November 2020) - Donadeu, Laura; Revilla-López, Eva; Jarque, Marta; Crespo, Elena; Torija, Alba; Bravo, Carles; Los Arcos, Ibai; Meneghini, Maria; Favà, Alex; Román, Antonio; Monforte, Víctor; Bestard, Oriol
Abstract: Monitoring cytomegalovirus (CMV)-specific cell-mediated immunity (CMI) is useful in predicting late-onset CMV infection after solid organ transplantation, but few data have been reported after lung transplantation (LT). CMV CMI against 2 CMV antigens (IE-1, pp65) was evaluated in 60 seropositive LT at 6-month prophylaxis withdrawal. LT with late-onset CMV infection showed significantly lower (IE-1)CMV CMI than patients without ( P  = .045), and was more evident in patients developing high viral loads ( P  = .010). (IE-1)CMV CMI independently predicted high first late-onset viral replication (odds ratio, 4.358; 95% confidence interval, 1.043–18.215). CMV-specific CMI may be useful in CMV preventive strategies after LT.